An application of 3D logical structure in a DHT paradigm for efficient communication in MANETs / Shahbaz Akhtar Abid - Abid, Shahbaz Akhtar (2014)

(untitled)
In the last few years, Distributed Hash Table (DHT) has come forth as a useful additional technique to the design and specification of spontaneous and self-organized networks. Researchers have exploited its strengths by implementing it at the network layer and developing scalable routing protocols for mobile adhoc networks (MANETs). This study investigates the features, strengths and weaknesses of existing DHT-based routing protocols and identifies key research challenges that are vital to address, namely the mismatch problem, merging of logical networks, and resilience of logical structure. This thesis proposes a novel three-dimensional DHT-based routing protocol, named 3D-RP, which exploits a 3D logical space that takes into account the physical intra-neighbor relationships of a node and exploits a 3D structure to interpret that relationship. The three- dimensional logical space (3D-LS) gives a node the liberty to exactly interpret the physical relationship of nodes in the three-dimensional logical structure (3D-LIS), which helps to avoid the mismatch problem. This work also addresses the mismatch problem between the overlay network and the physical network in P2P protocols over MANET that works at the application layer. Moreover, this study presents a novel protocol for content sharing in P2P over MANET that is a variation of 3D-RP and exploits a 3-dimensional overlay and 3D space at the application layer to avoid the mismatch problem in P2P over MANETs. The inefficiency of merging logical networks is addressed with the proposed leader-based approach (LA), which detects and merges DHT-based logical networks. LA is embedded in 3D-RP and MDART to compare their performance when merging two logical networks. 3D-RP and LA are compared with the existing schemes on the basis of path-stretch ratio, end-to-end delay, packet delivery ratio, false negative ratio, loss ratio, and routing overhead. Simulation results show that the proposed protocols effectively handle the mismatch problem, merging of logical networks, and resilience of the logical structure.